Diode-pumped wavelength-switchable quasi-three-level Nd:LiLuF4 laser on the 4F3/2→4I9/2 transition - Chu Chu; Zhenhua Du; Nguyentuan Anh; Yuzhao Li (PLoS ONE, 2025)
We first demonstrate a continuous-wave (CW) wavelength-switchable quasi-three-level Nd:LiLuF 4 laser operating at 4 F 3/2 → 4 I 9/2 transition. By shifting the pump beam waist location in the Nd:LLF, switching between single-wavelength (SW) and dual-wavelength (DW) operation can be achieved. The maximum SW output power of 4.03 W at 905 nm was obtained with a slope efficiency of 27.9% relative to the absorbed pump power. Furthermore, DW operation at 905 and 909 nm yielded the highest total output power of 3.21 W. Additionally, SW emission at 909 nm also reached a maximum output power of 2.21 W. Since the switching between SW and DW laser emissions is realized without introducing additional intracavitary losses, the method proposed in this paper provides a new approach for achieving high-power solid-state lasers with wavelength-switchable operation.